The Communicative Dimension of Personal Autonomy - Pisani, Keith (Conatus - Journal of Philosophy, 2024)
Paul Benson and Andrea C. Westlund have proposed conceptualising personal autonomy in terms of the readiness to respond to criticism that targets the agent’s actions and intentions (Benson) or commitments (Westlund). While incorporating this dialogical facet into a theory of personal autonomy is a step in the right direction, a theory of personal autonomy that is exclusively construed in terms of this facet and that posits discursive accountability as the sole criterion against which actions, choices, and commitments can be judged as autonomous or not is too restrictive and entails counterintuitive ideas. In this article, an alternative conceptualisation is proposed, one that avoids reductively construing personal autonomy exclusively in terms of the discursive and communicative facet and that conceptualises this facet in terms of communicative spaces which agents can claim authority over and in which and through which they can take ownership of claims, actions, and commitments. This alternative conceptualisation is initially formulated – by way of analogy – in terms of the normative requirement to respect the physical space of individuals. The article also outlines a set of conditions which indicate when one should claim authority over communicative spaces and the manner in which one takes ownership of claims, actions, and commitments in order to be autonomous.